POVERTY AND ECONOMIC INEQUALITY IN BANGKA BELITUNG - Illiana; Anggiani, Hikmah; Linda Mahanani, Kurnia; Fauzi, Ahmad (JAMBE: Jurnal Akuntansi Manajemen Bisnis dan Ekonomi, 2025)
Abstract: Bangka Belitung Islands Province, despite its rich natural resources, still faces major challenges related to poverty and economic inequality. The unequal distribution of wealth and access to economic opportunities are major obstacles to improving people's welfare. This article analyzes the factors causing poverty and inequality in Bangka Belitung, and evaluates the effectiveness of local government policies in addressing them. The study uses quantitative data analysis from BPS and other secondary data, as well as a review of related literature. The results of the study indicate that unequal distribution of resources, limited access to education and health services, fluctuations in commodity prices, and lack of economic diversification are the main factors causing poverty and inequality. Evaluation of poverty alleviation policies shows an increase in several indicators, but their effectiveness is still limited due to the lack of coordination between sectors and community empowerment. This study concludes that a more comprehensive and integrated poverty alleviation and inequality reduction strategy, with a focus on economic diversification, improving the quality of human resources, and community empowerment, is very important to realize sustainable and equitable economic development in Bangka Belitung